2007
DOI: 10.1002/nau.20458
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nocturia in a Korean population aged 40 to 89 years

Abstract: Aims: The purpose of this study was to evaluate the prevalence of nocturia in Korea, to examine the relationship between nocturia and demographic variables, and to determine the impact of nocturia on daily living. Methods: A national telephone survey using quota sampling methods was conducted in Korea. The clinically validated computer-assisted telephone interview approach was used for the survey. Results: Of 2005 subjects (1,005 women and 1,000 men) interviewed, 33.5% reported voiding once per night and 48.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 40 publications
8
41
0
Order By: Relevance
“…Voiding at least once nightly tended to be reported more frequently in younger women than in younger men (20.4% to 43.9% and 11% to 35.2%, respectively), but was equally common or more so in men in older age groups. 3,12,26,31,39 In particular Tikkinen et al observed that young women (18 to 29 years old) are more than 10 times more likely to have nocturia than young men (prevalence ratio 11.5) in the Finnish population studied. 31 However, some studies report a similar rate of nocturia in men and women across all age groups.…”
Section: Prevalence Of Nocturiamentioning
confidence: 94%
“…Voiding at least once nightly tended to be reported more frequently in younger women than in younger men (20.4% to 43.9% and 11% to 35.2%, respectively), but was equally common or more so in men in older age groups. 3,12,26,31,39 In particular Tikkinen et al observed that young women (18 to 29 years old) are more than 10 times more likely to have nocturia than young men (prevalence ratio 11.5) in the Finnish population studied. 31 However, some studies report a similar rate of nocturia in men and women across all age groups.…”
Section: Prevalence Of Nocturiamentioning
confidence: 94%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]78,79 Many cross-sectional studies after the millennium have shown an independent association of older age with nocturia after multivariate analysis.…”
Section: Agingmentioning
confidence: 99%
“…With regard to sex difference, there are three different findings for the prevalence of nocturia: (i) it is equal in both sexes; 14,17,20,21,26,79 (ii) it is higher in women; 15,22,23,33 and (iii) it is higher in men. 13,16,27 Tikkinen et al reported that women younger than 50 years had more nocturia than men of the same age, but that the prevalence of nocturia increased twice as rapidly in men as among women with aging.…”
Section: Sexmentioning
confidence: 99%
See 2 more Smart Citations